A billion bootstraps - Phil Smith (McGraw-Hill, 2007)
A Billion Bootstraps unearths the roots of the microcredit revolution, revealing how the pioneering work of people such as Dr. Muhammad Yunus-winner of the 2006 Nobel Peace Prize-is giving hope to billions. Philanthropist and self-made millionaire Phil Smith and microcredit expert and consultant Eric Thurman provide a riveting narrative that explores how these small loans, arranged by barefoot bankers,